Benefits of gastric bypass in the treatment of obesity: An overview (International Seven Journal of Health Research, 2024)
Introduction: Obesity is a health condition that has become increasingly common worldwide and is associated with various comorbidities. The treatment of obesity can involve lifestyle changes, medication or bariatric surgery. Gastric bypass is one of the most widely used techniques in the surgical treatment of obesity and has been shown to be effective in terms of weight loss and improving comorbidities. Methodology: A bibliographic review was carried out in the PubMed database, searching for articles published between 2010 and 2022, using the keywords "gastric bypass", "obesity", "comorbidities" and "effects". Results and Discussion: The studies evaluated showed that gastric bypass is an effective technique for treating obesity, with significant weight loss and improvement in comorbidities such as diabetes, hypertension, dyslipidemia and sleep apnea. In addition, gastric bypass has shown beneficial effects on quality of life and reduced mortality. Although gastric bypass is an effective technique, its indication must be carefully assessed, taking into account the severity of obesity and the presence of comorbidities. It is important that patients are properly informed about the risks and benefits of the technique, and that they are followed up by a multidisciplinary team after surgery. Conclusion: Gastric bypass is a safe and effective technique for treating obesity, with a positive impact on weight loss, improvement in comorbidities and patients' quality of life. However, it is important that the technique is carefully indicated and that patients are followed up by a multidisciplinary team after surgery.